PERSEPSI MASYARAKAT TERHADAP LEMBAGA KEUANGAN SYARIAH - Mu’allim, Amir (Islamic University of Indonesia, 2003)
Some of elements in our society have responded the expansive development and growth of syariah banking contemptuously, moreover, among some moslems themselves.The contemptuous view of Islamic banking showed by peopleâs trust for Syariâah Banking has been still relatively low. It shown by the moslem participation on investment and capital movement. Indeed, some of moslem intellectuals have criticized syariah banking, they considered of the transactions done by Islamic bankings, even, in contrary with its own-concept. In other words, itâs in compatible with syariâah spirit. The contemptuous view canât be separated from capitalism economic thatâs been deeply rooted in our society. Learning the problem surrounding syariâah finance institution and some of its positive value, itâs urgently required for this institution to improve its profesionality, in order to arise its image, next in future it hopefully able to spread wider merciful benefit . The effort increasing profesionality have to more attention of the relationship between syariâah finance institution and consumers, a commitment of continuous inovation and also a balanced consideration of decision maker research. Operationally, profesionality improvement of syariâah finance institution able to apply the Criteria Grade of Syariah banking Choice in Yogyakarta as its measurement. Key words: Persepsi, Pandangan, Lembaga Keuangan Syariâah, Profesionalitas.